Usability Evaluation of the Smartphone User Interface in Supporting Elderly Users from Experts' Perspective - Salman, H.M. (Institute of Electrical and Electronics Engineers Inc., 2018)
Despite the necessity for smartphones to be designed to better accommodate the elderly user, currently available smartphone user interfaces (UIs) do not appear to be optimized for that purpose. The objectives of this paper are to identify the potential usability problems among elderly adults when interacting with a smartphone's UI, and recommend improvements to UI designs. The heuristic evaluation technique was used to determine the anticipated usability problems. SMASH, a set of 12 usability heuristics for smartphone and mobile applications was applied within a controlled environment, with five experts with the necessary competence to perform the evaluation. The results of the study indicated that there were 27 usability problems and 27 heuristic violations encountered. 'Minimize the user's memory load' and 'match between system and real world' were the two most frequently violated heuristics. This study was complemented by testing with elderly people, and the results show that 79.17 of the problems experienced by the elderly were predicted by the experts. Usability problems were classified into four categories: 1) appearance; 2) language; 3) dialogue; and 4) information. Problems categories were further divided into sub-categories, and design solutions were suggested for each sub-category. This study's findings contribute to understanding the problems that hinder elderly users in using smartphones and provide valuable feedback to designers of smartphone technology regarding improvements to the UI to better suit the elderly. Â© 2013 IEEE.